Evaluasi Aplikasi DNA Barcode Lokus psbA-trnH pada Genus Momordica - Sumarlina, Sumarlina; Napitupulu, Tia Sofiani (Jurnal Biotek, 2023)
Molecular analysis has developed rapidly, one of which is through the application of the DNA barcode method which is supported by the existence of a genetic and molecular data center, namely NCBI. However, there is still no consensus on standard and universal DNA barcode region loci that can be used in plants of various taxa. One of the loci that has been collected in NCBI is psbA-trnH, including data from the genus Momordica. Therefore, this study aims to determine the effectiveness of DNA barcoding with the psbA-trnH in the genus Momordica. The study was conducted by collecting data on psbA-trnH sequence of the genus Momordica in the NCBI database. Sequence data that met the criteria were then aligned and analyzed using MEGA 11 software. The analyzes performed included sequence variation analysis, phylogenetic tree reconstruction based on the maximum parsimony and maximum likelihood methods with bootstrap of 1000x, and the calculation of genetic distance values based on pairwise distance with Kimura-2-Parameters (K2P) substitution model. The results showed that the psbA-trnH region fulfilled the three principles of selecting DNA barcode regions, namely standardization, minimalism, and scalability. The psbA-trnH region has been shown to be able to describe the genetic variation of the genus Momordica both at the interspecies and intraspecies levels, but it is still not effective enough to describe the phylogenetic between taxa, so it needs to be combined with other regional barcode region through further tests and studies.